2007
DOI: 10.1021/ac070277i
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Polymers as Antibody Mimics in Automated On-Line Fluorescent Competitive Assays

Abstract: An automated molecularly imprinted sorbent based assay (MIA) for the rapid and sensitive analysis of penicillin-type beta-lactam antibiotics (BLAs) has been developed and optimized. The polymers were prepared using penicillin G procaine salt as template (PENGp) and a stoichiometric quantity of a urea-based functional monomer to target the single oxyanionic species in the template molecule. Highly fluorescent competitors (emission quantum yields of 0.4-0.95), molecularly engineered to contain pyrene labels whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 21 publications
0
48
1
Order By: Relevance
“…The first method involves using a labeled template or an analogue derivative in a displacement or competitive assay 577,578 for the fabrication of MIP-based fluorescence sensors. For example, Sellergren et al 579 developed an automated molecularly imprinted sorbent based assay (MIA) based on a fluorescent competitive assay for the rapid and sensitive determination of penicillintype b-lactam antibiotics (BLAs) in biological samples. Generally, the analyte and a constant amount of labeled fluorescent analogue were packed in a reactor in the assay, and then the fluorescence of the labeled derivative was measured which was eluted from the sorbent by using a desorbing solution.…”
Section: View Article Onlinementioning
confidence: 99%
“…The first method involves using a labeled template or an analogue derivative in a displacement or competitive assay 577,578 for the fabrication of MIP-based fluorescence sensors. For example, Sellergren et al 579 developed an automated molecularly imprinted sorbent based assay (MIA) based on a fluorescent competitive assay for the rapid and sensitive determination of penicillintype b-lactam antibiotics (BLAs) in biological samples. Generally, the analyte and a constant amount of labeled fluorescent analogue were packed in a reactor in the assay, and then the fluorescence of the labeled derivative was measured which was eluted from the sorbent by using a desorbing solution.…”
Section: View Article Onlinementioning
confidence: 99%
“…Due to the specific nature of the interaction between the molecularly imprinted materials and selectable molecules, they have been employed in several analytical techniques, including liquid chromatography, 2 capillary electrophoresis 3 and capillary electrochromatography, 4,5 solid phase extraction, 6 and immunoassay determinations. 7 Molecularly imprinted polymers can be prepared following three different imprinting approaches. 8,9 The non-covalent procedure is the most widely used, because it is relatively simple experimentally and the complexation step during the synthesis is achieved by mixing the template with an appropriate functional monomer, or monomers, Vol.…”
Section: Introductionmentioning
confidence: 99%
“…21 The effect of the imprinted film thickness and polymerization time on the assay sensitivity was also investigated in the present study. Results indicated that when the plate was sealed and irradiated by UV irradiation for 12 h, lower IC 50 values (70 ± 4 mg L -1 ) and optimized competitive binding between MMZ and the HRP conjugate were observed.…”
Section: Condition Optimizationmentioning
confidence: 97%
“…Moreover, the production of antibodies for toxic substances or immunosuppressants is particularly difficult, because they have effects on metabolism and the immune system. 21 Some studies have attempted to design and synthesize artificial antibody to replace antibodies.…”
Section: Introductionmentioning
confidence: 99%